NEW STONE RELIEFS-ARCHITECTURAL DETAILS OF THE 14th – 18th CENTURIES FROM KUBACHI WITH ORNAMENT AND ARABIC INSCRIPTIONS - Mammaev, Misrihan Mamaevic (History, Archeology and Ethnography of the Caucasus, 2021)
The paper describes stone reliefs of the architectural decor of the 14th – 18th centuries with floral ornaments and Arabic inscriptions, discovered by the author in different years of the 20th – 21st centuries in the villages of Kubachi and Shiri, which are currently stored in museum collections. This paper is a continuation of a previous study of the stone reliefs from the village of Kubachi. The author provides the description of 20 reliefs, of which one (№ 12) is stored in the State Hermitage, seven others (№ 13–18, 20) – in the National Museum of the Republic of Dagestan (NMRD); eleven reliefs (№ 1–11) were revealed by us in Kubachi, and one relief (№19) – in the village of Shiri. The Kubachi reliefs are inserted in the structure of various residential or cult buildings (mosques) of the upper, middle and lower livings districts of the village. The reliefs had been obtained from the ruins of old buildings and installed into walls of new ones during their construction for decorative purpose. The integrity of the reliefs varies: some remained in a satisfactory condition, some have defects (break-offs, splits, etc.), others are incomplete, i.e. in fragments. Most of the reliefs considered in the article were drawn with estampage prints, which were then transferred to A1 paper sheets with the use of ink. The restoration of the broken-off details of the decoration of the reliefs № 7 and 16 was carried out by us. The Arabic inscriptions of some reliefs (№ 13–14), which are kept in the National Museum of the Republic of Dagestan, have not been translated into Russian due to the difficulty of reading or poor integrity. Many reliefs of the 14th – 18th centuries with floral ornaments and Arabic inscriptions, found in the masonry of the walls of some residential and religious buildings, especially the quarter mosque in the lowest part of Kubachi, are still not included in the article. The location of the reliefs in the upper parts (third floor) of buildings erected on a very steep slope makes it impossible to photograph them properly. The dating of some reliefs (№ 1–4, etc.) is preliminary. It can be further clarified on the basis of analogies after the publication of unpublished reliefs preserved in the village of Kubachi and those stored in museums – the State Hermitage and NMRD. Accurate dating of medieval art monuments in Kubachi without dates is one of the challenges in studying them. Description of the reliefs revealed in Kubachi is given in the order of recording them at different times and in different districts of the old part of the village.